COVID‐19 infection in CVID patients: What we know so far - Niels Weifenbach; Alisha Jung; Stefan Lötters (Immunity, Inflammation and Disease, 2021)
Abstract Introduction In patients with common variable immunodeficiency (CVID), immunological response is compromised. Knowledge about COVID‐19 in CVID patients is sparse. We, here, synthesize current research addressing the level of threat COVID‐19 poses to CVID patients and the best‐known treatments. Method Review of 14 publications. Results The number of CVID patients with moderate to severe (~29%) and critical infection courses (~10%), and the number of fatal cases (~13%), are increased compared to the general picture of COVID‐19 infection. However, this might be an overestimate. Systematic cohort‐wide studies are lacking, and asymptomatic or mild cases among CVID patients occur that can easily remain unnoticed. Regular immunoglobulin replacement therapy was administered in almost all patients, potentially explaining why the numbers of critical and fatal cases were not higher. In addition, the application of convalescent plasma was demonstrated to have positive effects. Conclusions COVID‐19 poses an elevated threat to CVID patients. However, only systematic studies can provide robust information on the extent of this threat. Regular immunoglobulin replacement therapy is beneficial to combat COVID‐19 in CVID patients, and best treatment after infection includes the use of convalescent plasma in addition to common medication.